2019
DOI: 10.1177/1756287219854923
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of Roystonea regia lipid extract (D-004) and terazosin in men with symptomatic benign prostatic hyperplasia: a 6-month study

Abstract: Background: Benign prostatic hyperplasia (BPH), a common urological disease in aging men, frequently produces lower urinary tract symptoms (LUTS). Clinical studies have shown that terazosin relaxes the smooth muscle of the prostate and bladder, facilitates bladder emptying, improves LUTS, increases maximum urinary flow, and reduces the residual volume of urine. D-004, a lipid extract of the fruit of the Cuban royal palm (Roystonea regia), presents a similar efficacy to Saw palmetto. Clinical studies have demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…13 The key to treating enlarged prostate is to suppress conversion of testosterone into DHT with reduced side effects. Many studies have attempted to develop 5ARI from natural products such as clinical drug candidates; these include cocoa phenolic extract, 14 lipid extract of Roystonea regia fruits, 15 Piper nigrum leaf, 16 and saw palmetto. 17 Cranberries (Vaccinium macrocarpon) are widely consumed for a variety of health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…13 The key to treating enlarged prostate is to suppress conversion of testosterone into DHT with reduced side effects. Many studies have attempted to develop 5ARI from natural products such as clinical drug candidates; these include cocoa phenolic extract, 14 lipid extract of Roystonea regia fruits, 15 Piper nigrum leaf, 16 and saw palmetto. 17 Cranberries (Vaccinium macrocarpon) are widely consumed for a variety of health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Ten trials randomized men (n = 2972) to phytotherapy versus active component [ 24 , 25 , 26 , 29 , 31 , 50 , 54 , 62 , 71 , 72 ]. Six RCTs compared Sr to an active comparator and reported non-significant changes in TPV from baseline (-7% to –2% or -2.0 ml to -0.7 ml) [ 24 , 26 , 29 , 31 , 50 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…A single trial reported significant TPV change from baseline after Sr 320 mg once daily (-14.5%, p <0.001) or Sr 160 mg twice daily for 12 months (-9.6%, p <0.001) [ 72 ]. Two non-Sr trials reported significant reduction in TPV as compared to baseline (-5.6% and -10.8%) [ 25 , 71 ]. Six trials reported non-significant changes in PSA as compared to baseline or to comparator (-15% to +10% or -0.3 ng/dl to +0.2 ng/dl) [ 24 , 29 , 31 , 50 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the average size of the prostate was reduced in both groups, this reduction reached statistical significance only for D-004. Both treatments were safe, while D-004 was better tolerated than terazosin [ 173 ].…”
Section: Medicinal Plants Widely Used In the Treatment Of Bphmentioning
confidence: 99%